SURGICAL CHALLENGES IN CLIPPING LARGE ANEURYSMS IN DISTAL ARTERIAL TERRITORIES - Mugurel Petrinel Radoi; Milena-Monica Ilie; Razvan-Adrian Covache-Busuioc; Horia Petre Costin; Luca-Andrei Glavan; Matei Serban; Antonio Daniel Corlatescu; Corneliu Toader (Romanian Neurosurgery)
Background